Design Thinking for Creating an Increased Value Proposition to Improve Customer Experience - Daniel Marco-Stefan Kleber (Faculty of Economic and Business, 2018)
Purpose of this conceptual study is the identification of design thinking approaches and underlying logic for increasing the value proposition to improve customer experience in today´s dynamic and fast-changing business environment. Method of research based on content analysis of distinctive streams in the literature on design thinking for delivering the increased value proposition. Core elements of design thinking were identified and combined with service-oriented thinking logics aiming at providing superior value proposition and thus to improve customer experience. Furthermore, the article elaborates on the delimitation of Design thinking from Designerly thinking, and a new model for enhancing customer value propositions, the wheel of Design thinking, was developed based on core elements of Design thinking approaches. This approach has a potential to shape and redefine existing markets and to improve adjustment of products and services to dynamic customers´ needs and demands.DOI: 10.15408/etk.v17i2.7311